The Influence of the Creative Problem-Solving Learning Model on the Creative Thinking Skills of Students of Natural and Social Science Subjects in Grade IV of SD Negeri 091264 Dolok Malela - Putri, Giana; Simamora, Aprido Bernando; Barus, Maria (Holistic Science, 2025)
This study aims to determine the effect of the Creative Problem Solving (CPS) learning model on students' creative thinking skills in the fourth grade science subject of SD Negeri 091264 Dolok Malela. This study used a quantitative approach with a pre-experimental method and a one-group pretest-posttest design. The sample in this study were all 22 fourth grade students. The research instrument was a descriptive test compiled based on four indicators of creative thinking, namely fluency, flexibility, originality, and elaboration. Data were analyzed using the N-Gain test and paired sample t-test. The results showed that there was an increase in the average score of creative thinking skills on all indicators after the application of the CPS model. The average posttest score was higher than the pretest, with the average N-Gain being in the moderate category. The paired sample t-test showed a significance value of less than 0.05, which means there was a significant difference between the pretest and posttest results. These findings indicate that the CPS model is effective in improving students' creative thinking skills. Thus, the Creative Problem-Solving learning model can be used as an alternative science learning strategy that can encourage students to think more creatively, actively, and independently in solving problems. This model is also relevant for application in thematic learning contexts in elementary schools.